Determination of TN for Ba6Mn4Mo15 (M = Cu, Zn) by neutron diffraction - Battle, P; Cussen, E (2001)
Determination of Néel temperature for Ba6MnMO15 (M = Cu, Zn) was discussed using neutron diffraction. The magnetic behavior of these material was found to be anisotropic and the interchain interactions were not negligible. The analysis showed that in both the cases, short-range magnetic coupling within the individual chains of pseudo-1D crystal structure produced a suspectibility maximum at a temperature higher than that at which the frustrated interchain interactions established long-range magnetic order.